Sensorless control using a full-order observer based on a novel flux model of high power interior permanent magnet synchronous motor - Lim, Young Seol; Lee, June Seok; Ryu, Joon Hyoung; Lee, Kyo Beum (Conference Proceedings - IEEE Applied Power Electronics Conference and Exposition - APEC, 2018)
This paper proposes a sensorless control method using a full-order observer based on a novel flux model of an interior permanent magnet synchronous motor (IPMSM) and the rotor position error compensation method in order to improve performance of the maximum torque per ampere (MTPA) operation. Since the novel flux model only uses the d-axis inductance, the IPMSM is regarded as the surface permanent mounted motor (SPMSM) in the novel flux model. However, the estimated rotor position error caused by the reluctance component exists in this model. In case of the high power IPMSM, the estimated rotor position error is quite large; therefore, it cannot be neglected and affects the performance of the MTPA operation. To solve this problem, the estimated rotor position error compensation method is proposed in this paper. The effectiveness of the proposed control method is verified by simulation results.
Keywords: Flux model; Full order observers; Improve performance; Interior permanent magnet synchronous motor; Maximum torque per ampere (MTPA); Maximum torque per ampere (MTPA) operations; Rotor position error compensations; Sensorless control method; Full-order observer; Interior Permanent Magnet Synchronous Motor (IPMSM)); Maximum Torque Per Ampere (MTPA); Novel flux model; Sensorless control